The Influence Of Interpersonal Communication And Economy Social Status Toward Ethnic Chinese - Javanese Ethnic Assimilation In Gunung Anyar Tambak Sub-Distric Area Surabaya City - Julianus Zaluchu (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
Research entitled “The influence of interpersonal communication and economy status toward Chinese-Javanese Ethnic Assimilation ini Gunung Anyar Tambak Sub District Area Surabaya City” base on idea that human who live in the midst multi ethnic scope. The misunderstanding could be happen in understanding these symbols, even though employed when interaction or communication between people who difference cultures, such as community in Gunung Anyar Tambak and surrounding, cause those area most of them settled Chinese and Javanese. This research intend to recognized : 1). Whether there are found influence interpersonal communication or not toward Chinese and Javanese ethnic assimilation in Gunung Anyar Tambak Sub District Area Surabaya City; 2). Whether there are found influence economy social status or not toward Chenese and Javanese ethnic assimilation in Gunung Anyar Tambak Sub District Area Surabaya City; 3). Whether there are found influence interpersonal communication and economy social status or not toward Chinese and Javanese ethnic assimilation in Gunung Anyar Tambak Sub District Area Surabaya City. Research approach used were interpersonal interaction and quantitative model. The results gained namely a) Interpersonal communication and economy social status simultaneously have significant influence toward Chinese and Javanese Ethnic assimilatin in Gunung Anyar Tambak Sub District Area Surabaya City; b) Partially interpersonal communicatin have significant influence toward Chinese and Javanese ethnic assimilation in Gunung Anyar Tambak Sub District Area Surabaya City; c) Partially economy social status does not have significant influence influence toward Chinese and Javanese ethnic assimilation in Gunung Anyar Tambak Sub District Area Surabaya City. To realizing assimilation between Chinese and Javanese, desirable people from both ethnic could be developing interpersonal communication in interaction, it is could be done by following meeting with surrounding community, openness each other in building communication and creating understanding (emphaty) on other event which forego another ethnic (out group) then will sprout out tolerance and solidarity inter ethnics.